Chitosan Silver and Gold Nanoparticle Formation Using Endophytic Fungi as Powerful Antimicrobial and Anti-Biofilm Potentialities - Ehab M. Mostafa; Mohamed A. Abdelgawad; Arafa Musa; Nasser Hadal Alotaibi; Mohammed H. Elkomy; Mohammed M. Ghoneim; Mona Shaban E. M. Badawy; Mostafa N. Taha; Hossam M. Hassan; Ahmed A. Hamed (MDPI AG, 2022)
Nanotechnology is emerging as a new technology with encouraging innovations. Global antibiotic use has grown enormously, with antibiotic resistance increasing by about 80 percent. In view of this alarming situation, intensive research has been carried out into biogenic nanoparticles and their antibacterial, antifungal, and antitumor activities. Many methods are available to enhance stability and dispersion via peroration of conjugate with a polymer, such as chitosan, and other bioactive natural products. Two marine fungi were isolated and identified as Aspergillus sp. and Alternaria sp. via sequencing of the 16S rRNA gene. In this work, these strains were used to form the conjugation of biogenic silver nanoparticles (AgNPs) from Aspergillus sp. Silv2 extract and gold nanoparticles (AuNPs) from Alternaria sp. Gol2 extracts with chitosan to prepare chitosan-AgNPs and chitosan-AuNP conjugates. A variety of imaging and analytical methods, such as UV-vis, X-ray powder diffraction (XRD), FTIR spectroscopy, transmission electron microscopy (TEM), and scanning electron microscopy (SEM) were utilized to characterize biogenic nanoparticles and conjugates. The biosynthesized Ag and Au nanoparticles along with the prepared conjugates were evaluated for their antimicrobial effects on Gram-negative and Gram-positive bacterial isolates, including Escherichia coli and Staphylococcus aureus. Both chitosan-AgNP and AuNP showed powerful antimicrobial activities compared to the control. On the other hand, chitosan-AgNP conjugation had better antibacterial ctivity than chitosan-AuNPs, which exhibited moderate activity against S. aureus and very low activity against E. coli. Furthermore, the antibiofilm potentials of the prepared conjugates were tested against four biofilm-forming bacteria, including P. aeruginosa, B. subtilis, E. coli, and S. aureus. The obtained results indicate that the chitosan-AgNP showed a promising anti-biofilm activities on all strains, especially S. aureus, while chitosan-AuNP conjugates showed moderate anti-biofilm against B. subtilis and weak activities against the other three strains. These results showed the superiority of chitosan-AgNP as a promising antibacterial as well as biofilm formation inhibitors.